Rus Africum IV : la fattoria Bizantina di Aïn Wassel, Africa Proconsularis (Alto Tell, Tunisia) : lo scavo stratigrafico e i materiali - De Vos, Mariette,; Maurina, Barbara, (Archaeopress Roman archaeology ;, 2019)
Aïn Wassel is the only rural site of Africa Proconsularis which has been excavated using the stratigraphic method and the detailed results are published in this volume thanks to an archaeological field survey of the surrounding rural region.